EDUCATION TOWARDS LITERACY AND DIGITAL CITIZENSHIP OF YOUNG PEOPLE: BEYOND “BEING ONLINE” - Monteiro, Angélica; Guedes Teixeira, Elsa; Leite, Carlinda; Barros, Rita; Fernandes, Preciosa; Soares, Filipa (Revista Conhecimento Online: Diversidade e Inclusão Social, 2022)
The effects of the pandemic crises in education have revealed social inequalities in the youth field but have also provided an opportunity to rethink the demands of education in an increasingly digital world. Framed on youth policies and on the 3 areas of Digital Citizenship defined by the Council of Europe – being online, well-being online and rights online – the present study explores policies and practices in youth digital literacy and citizenship education, with the aim of answering the following questions: What are the strands of digital citizenship education? How do teachers and school leaders perceive practices regarding young people and media and information literacy? What are the main challenges of digitalisation regarding social justice for young people facing vulnerable situations? Data were collected by a questionnaire submitted in 2020 to 120 teachers and school leaders from Portugal, Bulgaria, and Turkey, complemented by documental analysis. The results allow identifying the main strands of digital citizenship in education and the challenges of digital citizenship education. Despite the tendency of policies and European projects towards greater emancipation and empowerment of young people, the teachers and school leaders described practices that have aspects of a more regulatory nature. The conclusions supported the proposal of a model based on a critical approach with the aim of sustaining more inclusive and emancipatory digital practices, which favour greater conditions of social justice.